Internalisasi Budaya Religius Dalam Kegiatan Keagamaan Di MI Nur Riska Kota Lubuklinggau - Sujarwo, Sujarwo; Akip, Muhamad; Hamidi, Ahmad; Mukhlas, Mukhlas (Edification Journal : Pendidikan Agama Islam, 2023)
The purpose of this study is to determine the internalization of values, supporting and inhibiting factors as well as the contribution of internalization of religious culture through religious activities at MI Nur Riska Lubuklinggau. The approach in this study is qualitative with a type of case study research. Data collection techniques using observation, interview, and documentation methods. The results in the study suggest the internalization of religious cultural values in MI Nur Riska Lubuklingau through religious activities in accordance with expectations even though there are many cultural obstacles to globalization, the influence of friends and religious education from parents in addition to obstacles for supporters, namely support from parents and all teachers at MI Nur Riska Lubuklinggau, as well as the presence of students who are able to carry out Dhuha Prayers, Dzuhur and being a priest to his family and can be an example for other learners, and influence attitudes and traits can even increase emotional and spiritual intelligence.